PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKTURAL THINK PAIR SQUARE UNTUK MEMPERBAIKI PROSES PEMBELAJARAN DAN MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS III SD NEGERI 013 SINTONG - Yenti, Marni Yenti; Suanto, Elfis Suanto; ', Kartini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research aims to improve mathematics achievement in SD Negeri 013 Sintong by implement cooperative learning model approach to structural Think Pair Square. Subjects were students grade III who have the academic ability of the heterogeneous. This research is a class action research with two cycles. Each a cycle has four stages, the stages are planning, action, observation, and reflection. The result from the observation page shows that teacher-student activities had performed well after action has been made. An increase in the number of students who achieved at UH KKM end of each cycle compared to the number of students who achieve KKM on base score, the number of students who scored 20 and 30 more than to the development of the number of students who received grades 5 and 10. An action is deemed successful when the number of students that reached the Minimum Mastery Criteria had increased by the first and second daily exams. The number of students that reached Minimum Mastery Criteria from the base score, the first and the second daily exams, in that order are 15%, 30%, dan 55%. The result of this research shows that the Think Pair Square Cooperative Learning Approaches can improve the mathematics achievement from the students of class III SD Negeri 013 Sintong at the second semester of academic years 2014/2015. Keywords: Mathematics learning outcome, Cooperative learning, Think Pair Square, Class action research.